DEKONSTRUKSI KEPEMIMPINAN PEREMPUAN: DECONSTRUCT THE INTERPRETATION OF QS. AL-NISA/4: 34 - Nurpahlevi, Dwi Tio ; Rijal Ali (Takafu: Journal of Tafsir and Gender Perspective, 2024)
The relationship between men and women, both in the domestic and public spheres, is explained in QS. Al-Nisā/4: 34. The interpretations of ulama in the past were considered gender biased, but on the other hand, there are still things that can be applied from these interpretations, through deconstruction efforts. This article is here to understand QS. Al-Nisā/4: 34 in depth regarding the interpretations of commentators from time to time. The aim of this research is formulated in two ways: (1) examining the interpretation of the ulama towards the word qawwām and (2) deconstructing this interpretation to present a new alternative that is relevant today. This research uses a literature study with a descriptive-analytical model. The results obtained from this research show that the interpretations of previous scholars basically carry the same spirit, namely care and respect for women. Deconstruction efforts were carried out by analyzing the chronology of the revelation of the verse, which suggests egalitarianism. Apart from that, when the conditions and circumstances that make men become qawwām are transferred and owned by women, it can be said that women's leadership in the public sphere is no longer something that needs to be debated, considering that men and women have the same opportunity to have the potential.